Can climate finance achieve gender equity in developing countries? - Sam Wong (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
We develop the climate finance-gender equity framework in this paper and use the 'contextual-procedural-distributive' equity as a lens of analysis to examine how climate finance helps challenge, and reinforce, gender inequities in the mitigation, adaptation and disaster management strategies. Focusing on the examples of tree-planting, smart-agriculture and disaster information dissemination projects, this paper argues that climate finance can achieve gender equity if three aspects are critically considered: (1) how different incentives and preferences, between men and women, are shaped by their livelihood experiences and priorities, and what factors enable, and restrict, their access to resources; (2) how formal and informal participatory arena offers a genuine space for women, and men, to make decisions that empower them; and (3) how women's practical and strategic needs are met and the contradictions resolved. This paper also suggests that climate finance needs to address and challenge unequal socio-political arrangements, such as access to land rights, that help perpetuate gender inequities.
Keywords: A14; B53; Q2; Q50; 330; climate finance; gender equity; access; land rights; Green Climate Fund